THE PROBLEM OF SOVEREIGNTY IN THE MACROHISTORICAL POLITICAL PERSPECTIVE - Гайко, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The article analyzes the macrohistorical perspective of the study of sovereignty in the framework of political theory represented by a world-system analysis, the war-taxation theory of the state and political Marxism. The relevance of the approach proposed by macro-political theories for studying the current state of sovereignty is considered. The theoretical prerequisites for the formation of these theories are investigated, which were caused by the search for fundamentally new approaches in the 1970s. in analysis of modern political and state institutions, attention is focused on the influence of the creative heritage of M. Weber in the process of conceptualization of macrohistorical political theories. The basic theoretical approaches of world-system analysis (I. Wallerstein, J. Arrigi), the war-taxation theory of the state (Ch. Tilly, W. McNeill, M. Mann) and political Marxism (R. Brenner, P. Anderson, B. Teschke) to the process of formation and development of states during the Modern era are analyzed. In this article the problem of sovereignty is examined through an analysis of the prerequisites for the formation of basic state institutions in a historical perspective, which is the main approach of macrohistorical political theories. It is revealed that, despite the differences in approaches, the world-system analysis and the war-taxation theory of the state can be compared as the external and internal contours of the sovereignty problems in the historical process of the formation and development of European states during the Modern era, special attention is paid to the role of economically determined social transformations of Modern era in the framework of the theoretical approach that is offered by political Marxism. The similarities are noted in the approaches of the analyzed theories to the process of formation of modern type of states, which are specified in the following positions: modern type of states as a unique phenomenon in Western Europe, the special role of capitalism in the process of socio-political and economic transformations of Modern era, a successful configuration of factors in the historical process that led to the emergence nation state, achieving a balance between the interests of diverse groups, structural socio-political and economic changes as a response to external and internal challenges, the interdisciplinary nature of theories.